Instâncias de narração no jornalismo em quadrinhos : uma análise sobre a produção brasileira da agência Pública - Medeiros Neto, José Sampaio de (2018)
The present research investigates how the specificities of the reading pact predicted in journalism are manifested in comic journalism. Values such as objectivity, impartiality and neutrality, as well as the temporalities characteristic of journalistic production routines will be tensioned with the characteristics of the comic system. Brazilian comic reports published by the public agency of investigative journalism will be analyzed. The first chapter will be devoted to a history of possible approximations between the two terms, from the appearance of strips and cartoons published in newspapers to the process of legitimizing the quadrinistic format as a journalistic possibility, institutionalized with the emergence of the term graphic journalism and the publication of several articles in major circulation magazines. This consolidation process will also be evaluated in its thematic bias. Special emphasis will be given to possible reasons for a prevalence of conflict patterns. The second chapter will focus on how narrative categories are mobilized by graphic journalism, especially the concepts of graphic style and narrator-reporter. An approximation of this genre is also identified with literary journalism, especially with Tom Wolfe's new journalism. A first moment will be devoted to the attempt to understand the different ways in which graphic style can manifest itself in comic book journalistic narratives, more precisely how the traces of copyright can affect the specific documentary record in the journalistic reading pact. To deal with these tensions, we start with the concept of graphic visual style, more specifically the concept of graffiti, found in the work of Philippe Marion. In a second moment he will investigate the instance of narration itself, how the reporter-narrator or narrator-reporter enunciates his history based on criteria pertinent to his profession, as well as the natural tension caused by making available a 'product' that is supports in 'non-fiction' reports in a format usually recognized for its fanciful plot. Thus, it is aimed to know how the diegetic process in comic journalism, especially when the reporter is inserted in it, thus creating a kind of avatar-reporter. In the third chapter, four comic reports made available by A Pública will be examined from the criteria listed in the comics system (Groensteen, 2015), namely: narrative voices, graphic style, space and arthropology.